2017
DOI: 10.1123/jab.2016-0181
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Force-Velocity Mechanical Profile After Short Resistance Training Programs Differing in Set Configurations

Abstract: The main aim of this study was to analyze the effect of resistance training programs differing in set configuration on mechanical force-velocity profiles. Thirteen participants performed 10 unilateral knee extension training sessions over 5 weeks. Each limb was randomized to one of the following set configurations: traditional (4 sets of 8 repetitions at maximum intended velocity, 10RM load, 3-min pause between sets) or interrepetition rest (32 maximum intended velocity repetitions, 10RM load, 17.4 s of rest b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…The intercepts with force axis and velocity axis were calculated to determine the predicted force in isometric conditions (F 0 ) and maximal theoretical velocity (V 0 ), respectively. The F-v profile was calculated as the slope of the F-v linear relationship, using the following equation 25,26,35 : Finally, the theoretical maximal power (P max ) was calculated as in the previous F-V studies 23,26,35,36 , pertaining to jumping performance:…”
Section: Data Processing and Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The intercepts with force axis and velocity axis were calculated to determine the predicted force in isometric conditions (F 0 ) and maximal theoretical velocity (V 0 ), respectively. The F-v profile was calculated as the slope of the F-v linear relationship, using the following equation 25,26,35 : Finally, the theoretical maximal power (P max ) was calculated as in the previous F-V studies 23,26,35,36 , pertaining to jumping performance:…”
Section: Data Processing and Outcome Measuresmentioning
confidence: 99%
“…Inverse linear relationship between force/torque and linear/angular velocity has been documented for several multi-joint movements 22 . It has been shown that performing resistance exercise can alter the F-V profile 19,23 and that these changes in F-V profile depend on the type of resistance exercise 19 . It was also shown that athletes of different sports are characterized by substantially different F-V profiles 24 .…”
mentioning
confidence: 99%
“…This linear approach has been previously used to describe mechanical profiles in multi-joint exercises like jumping, cycling, running or lifting in many populations (Allison, Brooke-Wavell, & Folland, 2013;Zivkovic, Djuric, Cuk, Suzovic, & Jaric, 2017). However, research about the changes in the linear F-V relationship in response to different resistance training protocols is scarce (Djuric et al, 2016;Iglesias-Soler et al, 2017;Jiménez-Reyes, Samozino, & Morin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This study is focused on the set configuration which is defined by the repetitions performed in a set with regard to the maximum feasible number of repetitions (Iglesias-Soler et al, 2016;Mayo, Iglesias-Soler, & Fernández-Del-Olmo, 2014). In this sense, manipulating the number of repetitions contained in a set has been proven to be an effective way for inducing different types of neural and muscular adaptations (Iglesias-Soler et al, 2017;Morales-Artacho, Padial, García-Ramos, Pérez-Castilla, & Feriche, 2018;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation